The genome-wide analysis identified significant genomic loci explaining genetic variance for body conformation in Hanwoo (Korean cattle) cows - Heegun Lee; Dongjae Lee; Ji Min Kang; Seungwon Oh; Hyemi Do; Doo Ho Lee; Yeoungkuk Kim; Sung Jin Kim; Jihyun Son; Seung Hwan Lee; Duhak Yoon; Yangmo Koo (Journal of Applied Animal Research)
Genomic data and objective traits (body conformation, growth and carcass features) could increase efficiency in cow selection. GWAS on carcass traits of Hanwoo cattle have been published; however, only a few studies are about body conformation traits, which are significantly correlated with carcass traits. Hence, this study aimed to investigate the effect of selecting genomic regions for body conformation traits in Hanwoo cows (n = 13,500). Four body conformation traits (wither height, body length, body width and body depth) were measured in cows genotyped using the Axiom Bovine 60k v3 array. BTA4, 6, 14, 19 and 20 harboured significant SNPs, annotated to CYP7B1, FAM110B and TOX. Fat-related genes explained a higher proportion of body conformation traits than growth-related genes in this study. We ranked animals with favourable and unfavourable genotype combinations of highly significant SNPs against their GEBV. Both groups were statistically significantly distributed with considerable deviations, implying that significant genomic regions could not explain total genetic variance. These results and the reported assumption that steady selection of animals performed over generations derives new genomic regions that account for the phenotype show the potentiality of SNPs to be used as weight in the genomic selection of body conformation traits in the Hanwoo cow.